Modulation of expression and activity of intestinal multidrug resistance-associated protein 2 by xenobiotics - Tocchetti, Guillermo Nicolás; Rigalli, Juan Pablo; Arana, Maite Rocío; Villanueva, Silvina Stella Maris; Mottino, Aldo Domingo (Toxicology and applied pharmacology, 2016)
The multidrug resistance-associated protein 2 (MRP2/ABCC2) is a transporter that belongs to the ATP-binding cassette (ABC) superfamily. In the intestine, it is localized to the apical membrane of the enterocyte and plays a key role in limiting the absorption of xenobiotics incorporated orally. MRP2 may also play a role in systemic clearance of xenobiotics available from the serosal side of the intestine. MRP2 transports a wide range of substrates, mainly organic anions conjugated with glucuronic acid, glutathione and sulfate and its expression can be modulated by xenobiotics at transcriptional- and post-transcriptional levels. Transcriptional regulation is usually mediated by a group of nuclear receptors. The pregnane X receptor (PXR) is a major member of this group. Relevant drugs described to up-regulate intestinal MRP2 via PXR are rifampicin, spironolactone and carbamazepine, among others. The constitutive androstane receptor (CAR, NR1I3) was also reported to modulate MRP2 expression, phenobarbital being a typical activator. Dietary compounds, including micronutrients and other natural products, are also capable of regulating intestinal MRP2 expression transcriptionally. We have given them particular attention since the composition of the food ingested daily is not necessarily supervised and may result in interactions with therapeutic drugs. Post-transcriptional regulation of MRP2 activity by xenobiotics, e.g. as a consequence of inhibitory actions, is also described in this review. Unfortunately, only few studies report on drug-drug or nutrient-drug interactions as a consequence of modulation of intestinal MRP2 activity by xenobiotics. Future clinical studies are expected to identify additional interactions resulting in changes in efficacy or safety of therapeutic drugs.